Shape Memory Alloys and their Thermal Characteristics - Sundara Raman, R. (Asian Review of Mechanical Engineering, 2019)
The smart structures are sometimes called “intelligent” or “adaptive” structures, being a class of advanced structures having highly distributed actuators and sensors combined with structural functionality, distributed control functions and even computing architectures. The structures are able to vary their geometric configurations as well as their physical characteristics subject to control laws. These include piezoelectric, electrostrictives, magnetostrictives, ionic polymers, Shape Memory Alloys (SMA), and magnetic shape memory alloys (MSMAs). Development of smart structures involves the integration of active and passive material systems, often including the coupling of relevant mechanical, electrical, magnetic, thermal, or other physical properties. This can subject the active materials to large stress levels, cyclic loads, thermal loads, or environmental loads that result in non-linear responses and large variations in material properties. Smart materials are not only singular materials; rather, they are also hybrid composites or integrated systems of materials. Shape memory alloys (SMAs) are one of the major elements of smart hybrid composites because of their unique properties, such as shape memory effect, pseudo elasticity and high damping capacity. These properties in smart hybrid composites provide tremendous potential for creating new paradigms for material – structural interactions and demonstrate various successes in many engineering applications, such as vibration control, actuators in MEMS, and a variety of others.